2020
DOI: 10.1001/jamanetworkopen.2020.16377
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of High School Students’ Participation in Blood Donation and Registration as an Organ Donor

Abstract: Author Contributions: Drs Tat and Boss had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 5 publications
0
13
2
Order By: Relevance
“…In one study, 53 blood donation predicted willingness for both deceased and living anonymous organ donation. 44%–81% of blood donors were willing to become organ donors 41,42,46,49,51 . For deceased organ donation, blood donors were more willing to donate their organs than the general public or non‐blood donors 8,41,46 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study, 53 blood donation predicted willingness for both deceased and living anonymous organ donation. 44%–81% of blood donors were willing to become organ donors 41,42,46,49,51 . For deceased organ donation, blood donors were more willing to donate their organs than the general public or non‐blood donors 8,41,46 .…”
Section: Resultsmentioning
confidence: 99%
“…Blood donation was significantly and positively associated with having an organ donor card 43,45 or joining an organ donor registry 44 . 13%–72% of blood donors owned an organ donor card or were registered organ donors 9,46–51 . More blood donors (vs. non‐blood donors 47–51 or the general population 9,46 ) had signed a donor card or were registered organ donors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This overlap suggests that volunteer blood donors, who number in the millions each year in the United States (US) alone, 8,9 may be a fruitful source of potential organ donors. Consistent with this notion, results of prior surveys have noted a correlation between blood donor status and registration as an organ donor 3,10–12 . For example, Merz et al 3 observed that among the approximately 40% of the Dutch population who registered their decision in the country's opt‐in post‐mortem organ donor registry, 69% of active blood donors enrolled as an organ donor as compared to only 60% of the general population.…”
Section: Introductionmentioning
confidence: 84%